Recommended Principles and Guidelines on Human Rights and Human Trafficking - United Nations (United Nations, 2013)
The Recommended Principles and Guidelines have been developed in order to provide practical, rights-based policy guidance on the prevention of trafficking and the protection of victims of trafficking. The Commentary on the Recommended Principles and Guidelines on Human Rights and Human Trafficking aims at providing further concrete guidance on the prevention of human trafficking and the protection of victims of trafficking. States and intergovernmental organizations are encouraged to make use of the Principles and Guidelines, as well as the Commentary, in their own efforts to prevent trafficking and to protect the rights of trafficked persons.